Enhancing biology teachers’ competence through the Sasirangan Verse local wisdom learning media in Banjarmasin - Siti Ramdiah; A. Abidinsyah; Ria Mayasari (Journal of Community Service and Empowerment, 2025)
This community service activity aimed to enhance the competence of Biology teachers in developing and utilizing digital learning media based on local wisdom, specifically the Sasirangan Verse media. This innovation integrates the cultural heritage of South Kalimantan—particularly Sasirangan motifs and natural dyes—with Biology topics such as biodiversity, ecosystems, and adaptation, making the material more contextual and meaningful for students. The program involved Biology teachers from the MGMP (Subject Teacher Forum) in Banjarmasin. Initial observations revealed that most teachers had not yet applied digital learning media grounded in local wisdom, while students showed limited understanding of Sasirangan culture. The activity was conducted through workshops and mentoring, including training on how to apply Sasirangan Verse and integrate it into Biology lessons. The expected outcomes were improved teacher competence in utilizing digital, culturally rooted media as well as increased student motivation and comprehension of Biology concepts. This initiative supports the implementation of education while simultaneously contributing to the preservation of local culture in a sustainable manner.